2019
DOI: 10.22207/jpam.13.3.27
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Bacteriological Profile and Antibiotic Resistance Pattern of Catheter Associated Urinary Tract Infections in a Tertiary Care Hospital

Abstract: During the past three decades, especially in developed countries there are adequate and effective Hospital Acquired Infection (HAI) control programs and implementations are being focused. But in developing countries, due to lack of awareness and effective implementable infection control policies, there is no adequate comparative data to validate the safe healthcare delivery system. Thus this descriptive surveillance study was aimed to find the Incidence rate of Catheter Associated Infections (CA-UTIs) in a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Most CAUTI occurrences occur in hospitals, as evidenced by a study conducted at the Government Medical College and Haldwani Hospital (Nainital), where numerous CAUTI cases were discovered, and E.coli was determined to be the most common bacteria proven to be the cause [4]. Almost identical to the study showing that this bacterium is a prevalent infection found in hospital in patients with indwelling catheters [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most CAUTI occurrences occur in hospitals, as evidenced by a study conducted at the Government Medical College and Haldwani Hospital (Nainital), where numerous CAUTI cases were discovered, and E.coli was determined to be the most common bacteria proven to be the cause [4]. Almost identical to the study showing that this bacterium is a prevalent infection found in hospital in patients with indwelling catheters [5].…”
Section: Introductionmentioning
confidence: 94%
“…This was owing to the careful application of UTI bundles, which included hand cleanliness, aseptic procedures, a closed catheter drainage system, and personal protective equipment (PPE). This demonstrates that infection prevention may be managed successfully when health care are provided while in the hospital [5]. The UTI prevention and control bundle contains this management, and it is used as a catheterizationrelated control to reduce catheter-related UTIs.…”
Section: Introductionmentioning
confidence: 96%
“…Bölgesel direnç paternleri bilinirse ampirik tedavinin başarılı olma şansı çok daha yüksek olacaktır. 7 Bu araştırmada hastanemizden elde edilen E. coli kökenlerinde antibiyotik direncinin saptanması, cinsiyet ve yaşın antibiyotik direncine etkisi ve genişlemiş spektrumlu beta-laktamaz (GSBL) varlığının araştırılması amaçlanmıştır.…”
Section: Introductionunclassified